(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2018)
The capital in the bank is the important element in establishing it, because it maintains the banking sector in the event of exposure to losses or risks In addition to contributing to the provision of liquidity And protection of depositors’ money from potential and unexpected losses. There is also a relationship between the prices of shares and the indicators of the durability of the capital owned, considering that the shares are the components of the bank capital The study limited the indicators of capital to assets and capital to deposits, capital to loans and financial investments Where the most important conclusions are the damage to the detriment of shareholders in contrast to the depositors in the case of increasing the proportion of capital owned to assets because this increase will lead to a decline in the rate of return of capital in contrast to the increase of the ratio of capital to deposit property reflects a positive image to depositors and thus reflect the image Positive to the central bank, All the sample of the research was shown at the percentage of capital owned to the loans in a good manner and thus reflects a positive image on the margin of safety, either the most important recommendations on the banks to build protective foundations for the safety of the banking system The banks that show the capital of the property to the assets in a low rate to develop and draw up a plan for the purpose of balance between sources of funds and sources of uses.